Responsible tourism: cosmetics, utopia or reality? An analysis of the scientific literature. (21st March 2021) - Bernardo, Edgar; Pereiro, Xerardo
Responsible tourism is an increasingly important subject in tourism research, political discourse, and business practice. This paper reviews both the concept of responsible tourism, as well as the use of the concept of responsibility in the scientific literature of tourism from 1988 to 2018. We reflect on the social role of responsible tourism in relation to the term as concept, the practices of companies, and the communities and public administrations affected by it. The results are an exhaustive, complete and updated picture of the meanings of responsible tourism for academics; the paper also represents a debate focused on the moralisation of tourism and the critical meaning of responsible tourism as a concept, social practice of consumption, behaviour, social movement and agency for sustainable tourism change. Finally, a unified theory for responsible tourism is proposed, based on accountability, sustainability and behaviour, for a new definition of ethical tourism practice.